4b-3=3b+9

Simple and best practice solution for 4b-3=3b+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4b-3=3b+9 equation:


Simplifying
4b + -3 = 3b + 9

Reorder the terms:
-3 + 4b = 3b + 9

Reorder the terms:
-3 + 4b = 9 + 3b

Solving
-3 + 4b = 9 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
-3 + 4b + -3b = 9 + 3b + -3b

Combine like terms: 4b + -3b = 1b
-3 + 1b = 9 + 3b + -3b

Combine like terms: 3b + -3b = 0
-3 + 1b = 9 + 0
-3 + 1b = 9

Add '3' to each side of the equation.
-3 + 3 + 1b = 9 + 3

Combine like terms: -3 + 3 = 0
0 + 1b = 9 + 3
1b = 9 + 3

Combine like terms: 9 + 3 = 12
1b = 12

Divide each side by '1'.
b = 12

Simplifying
b = 12

See similar equations:

| 2(x^2+60x-200)=0 | | 14x+8=6x+12 | | 2x^5-32=0 | | 2(6x-4)=27 | | log(x+12)=3 | | 2x-[X+1]=5 | | 60=15d | | cos(x)=-3.8 | | 3x-61= | | X^2-14x+17=-6x+2 | | 4(3x+6)=-38+2 | | -2tk=20 | | 6X+5X+9X=180 | | x-x^2=0.19 | | 8-(2z-9)=8-3z | | X^2+3x-24=4 | | 8x^5-196x^4+153x^3-4096x^2=0 | | 12x+1=11x+16 | | 6x-30=5(3+x) | | (X^2+5)+(x^2+4)= | | 9x-(3x+14)=16 | | 3000=(200+8x)(15-.50x) | | -12x+3+12x= | | B(b+4)=140 | | 25=48-3x | | 2p-3(2-2p)=3(p-4)-24 | | 15ab-12a= | | 6(2m-3)-3m-2m=18+m | | 5x+4=53-2x | | 9(x-4)=54 | | X+131=x+61 | | 2x+3+y=4xb |

Equations solver categories